Dialogue Summary: Organizing a Care System for Older Adults in Ontario - Wilson, MG; Lavis, JN (My University, 2011)
A summary of what was learned from a stakeholder dialogue that addressed problems related to organizing a care system for older adults, options for addressing these problems, key implementation considerations, and next steps for organizing a care system for older adults in Ontario.
Keywords: care system; adults; Ontario